2007
DOI: 10.1074/jbc.m611117200
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia with Secondary Hypocalcemia due to a Missense Mutation in the Putative Pore-forming Region of TRPM6

Abstract: Hypomagnesemia with secondary hypocalcemia is an autosomal recessive disorder caused by mutations in the TRPM6 gene. Current experimental evidence suggests that TRPM6 may function in a specific association with TRPM7 by means of heterooligomeric channel complex formation. Here, we report the identification and functional characterization of a new hypomagnesemia with secondary hypocalcemia missense mutation in TRPM6. The affected subject presented with profound hypomagnesemia and hypocalcemia caused by compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(125 citation statements)
references
References 50 publications
3
122
0
Order By: Relevance
“…10,[14][15][16][17]20,31 Furthermore, five missense mutations leading to HSH have been described so far, from which only S 141 L and P 1017 R were further studied at the molecular level. 10,19 The S 141 L mutation found in the highly conserved serine 141 resulted in impaired trafficking of TRPM6 to the membrane, 10,18 while the P 1017 R mutation located in the putative pore-forming region is the only known example of a mutation affecting TRPM6-gating properties without altering assembly or trafficking events. 19 The remaining three-point mutations were found in three Polish families; however, the authors did not report whether HSH was a consequence of either TRPM6 trafficking or functional impairment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…10,[14][15][16][17]20,31 Furthermore, five missense mutations leading to HSH have been described so far, from which only S 141 L and P 1017 R were further studied at the molecular level. 10,19 The S 141 L mutation found in the highly conserved serine 141 resulted in impaired trafficking of TRPM6 to the membrane, 10,18 while the P 1017 R mutation located in the putative pore-forming region is the only known example of a mutation affecting TRPM6-gating properties without altering assembly or trafficking events. 19 The remaining three-point mutations were found in three Polish families; however, the authors did not report whether HSH was a consequence of either TRPM6 trafficking or functional impairment.…”
Section: Discussionmentioning
confidence: 99%
“…10,19 The S 141 L mutation found in the highly conserved serine 141 resulted in impaired trafficking of TRPM6 to the membrane, 10,18 while the P 1017 R mutation located in the putative pore-forming region is the only known example of a mutation affecting TRPM6-gating properties without altering assembly or trafficking events. 19 The remaining three-point mutations were found in three Polish families; however, the authors did not report whether HSH was a consequence of either TRPM6 trafficking or functional impairment. 20 Overall, 34 different mutations have been previously described, from which only five are point mutations, thus B85% of mutations are truncating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that expression of TRPM6 is regulated by dietary Mg 2ϩ and its channel activity is strongly inhibited by the intracellular Mg 2ϩ concentration ([Mg 2ϩ ] i ) (8,9). Generally, Mg 2ϩ -free solutions are used to measure the characteristic outwardly rectifying TRPM6 currents (8,10,11). Remarkably, TRPM6 contains a C-terminal ␣-kinase domain, of which the regulatory role on channel activity remains elusive (12)(13)(14).…”
mentioning
confidence: 99%
“…11,76 Functional consequences of the naturally occurring TRPM6 mutations include introduction of frame shifts, stop codons, or disruption of exon splice sites. 66,77,78 Only five missense mutations have been identified so far (Figure 2A) 66,77,78 ; their impact on TRPM6 function is discussed next.…”
Section: Role Of Trpm6 Channels In Renal Magnesium Homeostasismentioning
confidence: 99%